A catalyst applicable for gasification of biomass and a method using the same - Yap, Taufiq Yun Hin; Seenivasagam, Sivasangar (2013)
A method of producing hydrogen gas by decomposing lignocellulosic materials comprises the steps of providing a mixture of the cellulosic materials and a catalyst in a ratio of 0.2-1 to 0.2-1 by weight; heating the mixture at a temperature increasing rate of 5 to 200C min-1 to a temperature of 600 to 12000C to decompose the mixture to produce the hydrogen gas in the presence of an inert gas having partial oxygen of 0.5 to 10%, wherein the catalyst is calcined CaO-NiO solid doped with Ba-based derivative and/or Nd-based derivative.